Dental tourism in Hungary - Remenyik, Bulcsú; Molnár, Csilla (KSU Publ., 2018)
In dental tourism, the cost of treatment in the country of departure and the total budget (travel, accommodation, catering, further travel expenses) in the host country have the most important role to make the decision. In general, people can save 40-70 % of their money, depending on the nature and the location of the treatment. However, it is also a fact that under a certain threshold, below the savings amount, it is not «worth it» for the patient to travel. The geographic distance of the healthcare provider plays an important role in different types of treatment. For «minor interventions», such as dental care, it is not worth for health tourists to travel to other continents; Western European dental tourists typically travel to Eastern Europe. In case of larger, life-threatening surgeries, the necessity of intercontinental treatment is questionable firstly due to the long flight and, secondly, to the continuous post-treatment and possible complications. In scientific literature it is difficult to find accurate statistics about the relationship between the nature of treatments and the geographical distance of the sending/receiving country. Another aspect of decision-making is whether a relative or friend of the health tourist can accompany them to the treatment, and if it is possible, how big the total will be including the costs of the accompanying person. Generally speaking, the patients arrive with an escort to the destination country who can provide spiritual support and also nurse them.
Венгриядағы стоматологиялық туризм
Стоматологический туризм в Венгрии
Keywords: dental tourism; health tourism; marketing trends; a provider of medical services; intercontinental treatment